Pendampingan Legalitas Usaha Nomor Induk Berusaha pada Pelaku UMKM Fadhil Cake Dan Kue Basah Firmala - Nanda Cecharia; Rizkiyah Alvina Ramandhita; Rifda Salsabila Putri Kholiq; Nadiyah Anggun Eka Wardani; Nur Aisyah Risqiyah; Nafia Ilhama Qurratu’aini (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the main sectors supporting the Indonesian economy. Kedung Sumur Village and Bluru Permai Village are one of the small areas that have several unique Micro, Small and Medium Enterprises (MSMEs). In its development, these MSMEs experience obstacles such as a lack of understanding of the importance of NIB ownership as a form of Business Law for business actors in the food category. The research methods used in this study include quantitative and qualitative data collection through surveys, interviews, and documentation studies. The research sample will consist of fadhil cake MSMEs and Firmala wet cake MSMEs. For all business owners, the Business Identification Number (NIB) is an important component in the legitimization of their company.